Comparative analysis of capital structures in Latin America companies - Logreira-Vargas, Cristina; Pinos-Luzuriaga, Luis Gabriel; Tonon-Ordoñez, Luis Bernardo; Vásquez-Peñaloza, Lisseth (Revista Venezolana de Gerencia, 2025)
This article aims to provide a comparative analysis of the capital structure of large companies in the manufacturing sector of Colombia and Ecuador regarding company size, guarantees or tangibility, cost of debt, growth opportunities, reputation, and liquidity as determinant variables. Based on a sample of 509 manufacturing companies in Colombia and Ecuador, a panel data model was applied to estimate the determinants of the indebtedness of companies in this sector. The findings expose that in Colombia, the variables that influence the total indebtedness of companies are ROA, tangibility, and liquidity. In Ecuador, variables that influence the analysis of the total indebtedness of companies are ROA, size, tangibility, and liquidity. The Pecking Order Theory explains these results. This study contributes to understanding the determinants of companies’ financing types in Colombia and Ecuador, acknowledging that there are substantial differences between the economies of the two countries explained above, all by dollarization and the family structure of most companies in Ecuador and by more significant development in the Colombian stock market.